2019
DOI: 10.1002/jsfa.9563
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diet of the donor cows on in vitro measurements of methane production from wheat and corn incubated in various forage‐to‐grain ratios

Abstract: BACKGROUND Supplementation of ruminant diets with wheat and corn grains influences ruminal fermentation. In vitro fermentation is a methodology that can be used to screen feeds for their potential to produce enteric methane. However, there is evidence that the diet of the donor cows could impact the results of in vitro analysis. This research investigated the in vitro fermentation of wheat and corn grain when incubated in ruminal fluid from cows fed different grain types and different forage‐to‐grain ratios. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Condensed tannins from grape seeds have been shown to have a direct inhibitory effect on methanogenesis in vitro [ 44 ]. However, findings from experiments conducted in vitro do not always relate to what happens in vivo [ 34 , 45 ]. In the current experiment, the apparent lack of a major effect of grape tannins on methanogenesis is not surprising as there is great diversity in the total concentration and the different types of tannins present in different types and sources of grape marc [ 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Condensed tannins from grape seeds have been shown to have a direct inhibitory effect on methanogenesis in vitro [ 44 ]. However, findings from experiments conducted in vitro do not always relate to what happens in vivo [ 34 , 45 ]. In the current experiment, the apparent lack of a major effect of grape tannins on methanogenesis is not surprising as there is great diversity in the total concentration and the different types of tannins present in different types and sources of grape marc [ 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Is it due to starch degradation rate for example, or some unidentified factor in one grain or another? Perhaps also the outcome of feeding different diets may depend on the pre-existing state of the ruminal microbial population [ 9 ]. Different forages and grains have been compared and exotic additives tested in an effort to manipulate the fermentation process occurring in the rumen [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not all grains are equally effective in reducing methane production in the rumen, and there are indications that the response of methane production to different proportions of grains may not be linear [14]. Moate et al [15] found that dairy cows produced less methane when fed wheat than when fed maize or barley, and Herrera-Saldana et al [16] observed in vitro that maize grain has a lower rate and extent of degradation than barley grain.…”
Section: Introductionmentioning
confidence: 99%
“…A few reasons may account for the discrepancy between papers on methane production from different grain sources: 1. When working in vitro, grains should be incubated in ruminal fluid from animals adapted to that specific grain type [14]; in the case of Fellner et al [19], the donor animal (a dairy cow) was fed a forage diet. 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation